The tale as a pedagogical strategy to develop the inquiry in natural sciences - Castillo Duarte, Carmen Estela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This text provides results of the research work entitled: “The story as a pedagogical strategy to develop the competence of inquiry in natural sciences through didactic sequences” in eighth grade students of the “El Escobal” Agricultural Educational Institution of Ramiriquí (Colombia). The methodology in the research was developed from the qualitative approach, socio-critical paradigm under the research action, which allowed analysing the problem step by step; The stages that were developed were: diagnosis, planning and evaluation. The data was obtained through the design and application of didactic sequences, analysis, interpretation, description and reflection on the results obtained in the production of tales. The data was obtained through the design and application of didactic sequences, analysis, interpretation, description and reflection on the results obtained in the production of stories. From the subcategories: Understanding and construction of concepts, Ability to formulate questions and Use of scientific words, the development and strengthening of the competence of inquiry in natural sciences was verified, obtaining as a result the strengthening of communicative competences, base for the knowledge construction.